Penerapan Manajemen Risiko K3 pada Perusahaan Pabrikasi Kelapa Sawit Bagian Manual Handling - Najihah, Khoirotun; Safrina Ramadhani; Rupina Kanasia Situmorang; Alyandra Rizky Alfansyah Sinambela; Muhammad Dafi Rifatsyah (Jurnal Pembaruan Kesehatan Indonesia, 2025)
A work accident is an unexpected event that occurs in the workplace and results in physical injury, material loss or even death. According to Law No. 1 of 1970 concerning work safety, every work accident needs to be recorded and analyzed to prevent similar incidents in the future. front. There are many factors that cause work accidents in the workplace as well as the causes of work accidents in Palm Oil Manufacturing Company, including the following: Human Factors: Human error, lack of training, and non-compliance with safety procedures, use of inappropriate heavy equipment and machines Procedures are also a factor that can increase the risk of accidents. Environmental Factors: Unsafe workplace conditions, such as damaged equipment, lack of lighting and a dangerous environment can trigger potential work accidents in the workplace. The aim of this Community Services is to minimize the occurrence of work accidents. Service method with Implementating Risk Management. The results of the Community Services obtained were a change in knowledge from previously not knowing about Risk Management Concept to knowing and efforts to prevent work accidents. This Community Services activity is something that is really needed by Company workers as a forum for education or transfer of knowledge and information. beneficial for workers